LncRNA GAS5 Suppressed Proliferation and Promoted Apoptosis in Laryngeal Squamous Cell Carcinoma by Targeting MiR-26a-5p and Modifying ULK2 - Wang, Jian (Cancer Manag Res, 2021)
PURPOSE: Long noncoding RNAs growth arrest-specific 5 (GAS5) exerts important functions in modulating various tumor behaviors. However, the role of lncRNA GAS5 in laryngeal squamous cell carcinoma (LSCC) remains unknown. MATERIALS AND METHODS: Cell viability and apoptosis were, respectively, detected by cell counting kit-8 and flow cytometry, DIANA-LncBase V, Starbase, TargetScan and a dual-luciferase reporter gene assay were employed to assess the relationship among GAS5, miR-26a-5p and uncoordinated 51-like kinase 1 (ULK2), and quantitative reverse transcription-polymerase chain reaction (qRT-PCR) and Western blot were performed to detect the expression of autophagy-relative factors. RESULTS: The expression level of GAS5 was frequently decreased in LSCC cell lines, and up-regulated GAS5 inhibited AMC-HN-8 cells viability and induced apoptosis. More importantly, we found that GAS5 activated autophagy, with enhanced autophagy-related proteins after GAS5 overexpression. While down-regulated GAS5 had opposite results in Tu 177 cells, GAS5 was found to act as a microRNA sponge in a pathway to regulate miR-26a-5p and its target gene ULK2. MiR-26a-5p mimics inhibited apoptosis and autophagy, which were reversed by GAS5 and siGAS5 in AMC-HN-8 cells and Tu 177 cells, as well as ULK2 in AMC-HN-8 cells. Meanwhile, the concomitant downregulation of ULK2 and miRNA-26a-5p inhibitor decreased the miRNA-26a-5p inhibitor-induced apoptosis and autophagy. CONCLUSION: This is the first report of LncRNA GAS5 acting as a tumor suppressor in LSCC by regulating the miR-26a-5p/ULK2 axis, and it could be a new target for gene therapy in LSCC.